Aspirin and oral surgery - Ochyra, Dorota; Bałabuszek, Kamil; Pawlicki, Mateusz; Pawlicka, Marta; Mroczek, Anna; Ochyra, Bartłomiej (Journal of Education, Health and Sport, 2018)
Introduction: Acetylsalicylic acid (aspirin, ASA) belongs to nonsteroidal anti-inflammatory drugs group (NSAIDs), characterized by analgesic, antipyretic, anti-inflammatory properties. ASA blocks production of prostaglandins and thromboxanes due to non-competitive irreversible inactivation of cyclooxygenase 1 enzyme (COX1). Nowadays, ASA is most commonly used to inhibit platelet function and to reduce the risk of thrombotic events. The aim of the study: The purpose of this narrative systemic review was to analyse andsummarize available data on necessity of acetylsalicylic acid cessation before oral surgery.Material and method: Standard criteria were used to review the literature data. The search of articles in the PubMed and Google Scholar databases was carried out using the followingkey words: acetylsalicylic acid, oral health, oral surgery.Description of knowledge: According to some medical practitioners dosing acetylsalicylic acid (ASA) before tooth extraction should be stopped because of fear of bleeding complications. However, the cessation of aspirin may predispose patients to thromboembolic events. Most of the data indicates more benefits from continuation aspirin taking than treatment discontinuation. Summary: According to actual knowledge and conducted researches there is no need to stop dosing aspirin before oral surgery. The benefits of using aspirin are greater than the risk of bleeding.